A study on the impact of double external shocks on Chinese wholesale pork prices - Yu, Rui; Yang, Xiaoli; Mu, Endong (Frontiers in Veterinary Science, 2023)
Fluctuation in pork prices has always been a focus of academic attention. Provide practical reference for the impact of future outbreaks on the pork market according to the existing shocks, so that the pork market can achieve stable and sustainable development. After experiencing the double shock of African swine fever and the new crown pneumonia epidemic, Chinese pork prices have experienced substantial abnormal fluctuations.The article focus on the impact of double external shocks on pork prices, and compare the impact of African swine fever before and after the COVID-19 and constructs a natural experiment based on the time difference and regional difference in the occurrence of the epidemic. It uses a double difference model and a triple difference model to identify the impact of the above two types of external shocks on Chinese pork prices. The results found that both African swine fever and COVID-19 positively affected pork prices,, but the degree of impact was different, with African swine fever having a higher degree of impact than the New Crown Pneumonia epidemic; the degree of impact of African swine fever on pork prices differed before and after New Crown Pneumonia epidemic, with African swine fever causing a relatively higher increase in pork prices before New Crown Pneumonia epidemic; moreover, the degree of impact of a single African swine fever shock was higher than that of a double external. The possible reason for this is that the New Crown Pneumonia epidemic led to a decrease in market consumer demand, which prevented a further increase in pork prices.